Health implication of vitamin D on the cardiovascular and the renal system. (4th May 2021) - Al-Ishaq, Raghad Khalid; Kubatka, Peter; Brozmanova, Martina; Gazdikova, Katarina; Caprnda, Martin; Büsselberg, Dietrich
Abstract: Vitamin D regulates the calcium and phosphorus balance in the body. The activated form of vitamin D (1 α, 25-dihydroxyvitamin D) binds to vitamin D receptor which regulates genes that control cell proliferation, differentiation and apoptosis. In the cardiovascular system, the vitamin D receptor is present in cardiomyocytes and the arterial wall. A clear correlation between vitamin D level and cardiovascular diseases is established. Vitamin D deficiency affects the renin-angiotensin system leading to ventricular hypertrophy and eventually to stroke. While clinical trials highlighted the positive effects of vitamin D supplements on cardiovascular disease these still need to be confirmed. This review outlines the association between vitamin D and cardiovascular and renal disease summarising the experimental data of selective cardiovascular disorders.